FAKTOR PENENTUAN LOKASI PERUMAHAN DENGAN METODE AHP DI KABUPATEN LAMONGAN - Hammam Rofiqi Agustapraja; Siti Aminatur Rosidah (Universitas Teuku Umar, 2020)
Housing is a very important requirement for the community. The need for housing is increasing. The choice of housing is influenced by many factors, one of which is housing location. In this case, the influence of the location of housing on the Developer is analyzed. Housing location factors have the greatest influence in terms of property project development. This study conducted by a survey as well as distributing questionnaires to respondents registered in Public Housing and Settlements. The data analysis used is the AHP (Analytic Hierarchy Process) method. The results of this study indicate that the most important indicator land prices, environmental atmosphere or environmental conditions that are in the location of the housing, licensing and homeownership loans. Then from the dominant factors that influence the decision of the developer, namely from the aspect of land prices of 100%, from the aspect of the environmental atmosphere by 80%, from the licensing aspect by 50%, and from the aspect of KPR (Public housing loans), by 40%, then from the aspect of road conditions, trade and services by 20% and in terms of aspects of the market segment at 10%.Keyword : Housing Factor, Determination, AHP Method, Location of Housing